PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) DENGAN METODE DEMONSTRASI UNTUK MENINGKATKAN HASIL BELAJAR SISWA SMP NEGERI 4 SATAP LIKUPANG BARAT - Truly Daniel; Armstrong Sompotan; Jeferson Polii (Program Studi Pendidikan Fisika Jurusan Fisika Fakultas Matematika, Ilmu Pengetahuan Alam, dan Kebumian (FMIPAK), Universitas Negeri Manado, 2021)
This study aims to improve student learning outcomes. After following the learning process using the Problem Based Learning (PBL) learning model. This research was conducted at SMP Negeri 4 Satap Likupang Barat for the 2019-2020 academic year. The research method used was classroom action research (CAR) which was conducted in two cycles. Each cycle consists of four stages, namely, planning, implementation, observation and reflection. The subject of this research is class VIII, which consists of 18 students. The research instrument used is questions. KKM achievement has increased, namely the average student learning outcomes in cycle 1 of 55.5%. And increased in cycle 2 to 83.3%. This clearly shows that student learning outcomes have increased from cycle 1 to cycle 2. Thus, cycle 2 has met the indicators of achievement of results.